HAK EKS NARAPIDANA MENJADI ANGGOTA LEGISLATIF DITINJAU DARI HAK ASASI MANUSIA - Akhmad Nikhrawi Hamdie (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2016)
The study titled "Analysis of Ex-Prisoners Can Be a Legislative and Executive Seen From Law and Human Rights." This aims to understand and analyze regarding: (1) Implications of the Decision of the Constitutional Court (MK) of the Election Law of the former inmates in terms of human rights, and (2) the application for judicial review of the Election Law for the former inmates. Covering political rights of prisoners, ex-prisoners Completion rights could be members of the legislature and the executive as well as the promulgation of Law No. 10 of 2008 on General Election. Therefore, the formulations in a number of law above clearly violates the constitutional rights of citizens, for a prisoner who has undergone a criminal is a free citizen, have the same rights as other citizens who had never undergone a criminal (jail). On the whole, the constitutional rights of citizens of the former prisoner should be restored. Thus, the rights of citizens as guaranteed in the 1945 Constitution remains attached to the former prisoner. Just to remind Article 27 Paragraph (1) of the 1945 Constitution affirms, every citizen is equal before the law and in government and shall uphold the law and government with no exception. Or more pointedly, in Article 28 D Paragraph (1) of the 1945 Constitution which states that every person has the right to recognition, security, protection and legal certainty and equal treatment before the law, also Article 28 D paragraph (3) of the 1945 Constitution which contains, every citizen has the right to obtain equal opportunities in government. Restrictive formulations on the constitutional rights of citizens described above, is clearly a violation of human rights guaranteed under the Human Rights Act . Article 43 paragraph (1) of Law No. 39/1999 on Human Rights stated, every citizen has the right to choose and vote in elections, based on equal rights by voting in a direct, public, free and confidential in accordance with statutory provisions, also in Article 43 paragraph (3) , stipulates that every citizen can be appointed in any governmental positions.